IMPLEMENTASI GOOGLE MAPS API DENGAN PHP DAN MYSQL (KASUS : SISTEM INFORMASI PARIWISATA) - Agus Sidiq Purnomo (Faculty of Industrial Technology Universitas Islam Indonesia, 2015)
Yogyakarta is one of the provinces which became a tourist destination. There are so many tourist objects that have not been known by tourists, both the location and how to access that must be taken towards the attraction. Therefore, the information technology (IT) can be used to indicate the location of tourist attractions making it easier for travelers to reach the tourist attractions. As an initial step of literature used to collect various data about tourism. This app is designed based on the site map that was set before continuing with the implementation of applications using PHP and MySQL. This study focused on the use of the Google Maps API to show a map of the area attractions based on the coordinates of the region.